THE SOCIOLOGY OF ISLAMIC RITUALS: EXAMINING THE ROLE OF RELIGION IN SHAPING SOCIAL BEHAVIOR - Khoiriyah Khoiriyah; Ethan Tan; Ava Lee (Yayasan Adra Karima Hubbi, 2026)
Religion has long been a fundamental force in shaping social behavior, with Islamic rituals playing a central role in structuring moral and social conduct within Muslim communities. This study investigates the sociological dimensions of key Islamic rituals, including Salah (prayer), Sawm (fasting), Zakat (charity), and Hajj (pilgrimage), exploring how these practices influence individual and collective behavior. The aim of the research is to examine how Islamic rituals function as mechanisms for social cohesion, moral regulation, and identity formation. A qualitative research design was employed, utilizing semi-structured interviews and participant observation among Muslim individuals from diverse backgrounds. The findings indicate that these rituals not only foster personal spiritual growth but also strengthen social bonds, promote social responsibility, and encourage ethical conduct. Participants reported that Salah reinforced community unity, while Sawm and Zakat increased empathy and social responsibility. Hajj was viewed as a transformative experience, creating a sense of global Muslim identity. The study concludes that Islamic rituals are vital tools for fostering social solidarity and regulating social behavior, highlighting their dual role in personal devotion and community building. Understanding the sociological implications of these rituals provides valuable insights into the relationship between religion and society.